Improving Students' Awareness in Prevention of Sexual Violence Through Education and Guidance at Yarfin Integrated Islamic School - Julio Prayogo; Nur Rahma Ramdania Bado; Tedi Permana; Jahra Delia Wulandari; Shella Aldriyani; Sri Wahyuni; Meylani Sundari; Juanda Saputra DLT; Amanda Alifia; Willi Anwarudin (Abdimas Paspama, 2025)
The high rate of sexual violence against children in Indonesia is a serious concern, especially in the context of legal protection for children in educational environments. The Student Creativity Program aims to increase students' legal awareness in preventing sexual violence through a legal education approach and mentoring at the Yarfin Integrated Islamic Special School. Activities are carried out using legal counseling methods, interactive discussions, case simulations, and basic legal consultations that are adjusted to the age and capacity of students. Educational materials focus on children's rights according to laws and regulations, including the Child Protection Law and the Criminal Code (KUHP) related to sexual violence. Evaluations are carried out through pretests and posttests to measure the increase in students' understanding of legal aspects and preventive measures. The results of the activities show a significant increase in students' legal awareness, ability to identify forms of sexual violence, and courage to report to the authorities. This program is expected to be the first step in instilling legal literacy in children from an early age as a preventive effort against sexual violence in Islamic-based school environments.